2005
DOI: 10.1111/j.1523-1755.2005.09702.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease in an urban Mexican population

Abstract: Chronic kidney disease prevalence in this population is similar to that seen in industrialized countries. If these figures are similar to those of the entire Mexican population, only l out of 4 patients requiring renal replacement therapy in the country currently has access to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 29 publications
3
70
0
15
Order By: Relevance
“…In Mexico, CKD prevalence among the poor is two-to threefold higher than that of the general population, and the etiology is unknown in 30 % of ESRD patients. [23][24][25][26].…”
Section: Ckd In Developing Countriesmentioning
confidence: 99%
“…In Mexico, CKD prevalence among the poor is two-to threefold higher than that of the general population, and the etiology is unknown in 30 % of ESRD patients. [23][24][25][26].…”
Section: Ckd In Developing Countriesmentioning
confidence: 99%
“…However, ESRD of unknown origin is one of the most prevalent diagnoses due to a lack of prompt recognition of the disease, and is unclear whether hypertension is a cause or consequence of CKD [20]. Furthermore, a study including 3564 healthy subjects reported a prevalence of deteriorated creatinine clearance <60 mL/min of 37% [21].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Hypertension was present in 25% of the patients with a Ccr Ͻ60 ml/min and in 58% of those with a Ccr Ͻ15 ml/min. Proteinuria was detectable in 8.7% of those with Ccr Ͻ60 ml/min but increased to 12.5% in those with diabetes and hypertension (36). If we extrapolate the values published in the Third National Health and Nutrition Examination Survey (NHANES III) (37) for the population of LA in comparable age groups, there may be 47,000,000 patients with CKD in the region (Table 3).…”
Section: Prevalence Of Ckd Progression Risk Factors In Lamentioning
confidence: 99%